The Right to Privacy in International Law: Evolving Standards for Personal Data Protection in the Digital Era - Nafi’ah, Lutfiah Sholikhatun; Prastyanti, Rina Arum (Westscience Press, 2025)
Privacy and personal data protection are increasingly important issues in today's digital era. This article highlights the importance of recognizing privacy as a fundamental human right that must be protected by the state in accordance with applicable human rights principles and the constitution. Protection of personal data is becoming increasingly crucial because it is often a target for irresponsible parties. International regulations, such as the Universal Declaration of Human Rights and the General Data Protection Regulation (GDPR) in the European Union, provide a framework for the protection of personal data. This article also highlights a key challenge to protecting privacy, namely finding a balance between the need for security and individual privacy. Efforts such as developing specific laws on personal data protection, increasing public awareness, and enhancing international cooperation are urgently needed. Keywords: privacy, data protection, human rights, regulations, challenges.